ANALISA HIDRAULIKA SISTEM JARINGAN PIPA AIR BERSIH DESA TAMAN SARI - Ahmad Akmal Martnanda Surya Dharma; Sri Sunarjono (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2025)
Clean water is a fundamental need at the heart of individual and community life. Lack of clean water can have a significant impact on various aspects of life, including health, social and economic. In Indonesia, many villages are still facing a clean water crisis, one of which is Taman Sari Village. This problem requires a solution in the form of an efficient clean water pipeline network planning system to distribute water evenly and meet the needs of the community. This study aims to calculate the daily clean water needs of the Taman Sari Village community and design an efficient clean water pipe network system. In addition, this study also aims to determine the appropriate and efficient method of water distribution through pipe network analysis. Field survey data was used as the basis for calculations to ensure a system design that is relevant and appropriate to local conditions. The analysis and simulation process was conducted using EPANET software, which is capable of modeling water flow in pipe networks in a detailed and accurate manner. With the help of this software, water distribution calculations are performed to ensure the network design can optimally meet the clean water needs of the community. The research results are expected to not only provide a solution to the clean water crisis in Taman Sari Village but also become a planning model that can be applied in other areas with similar conditions. The implementation of this system is believed to increase access to clean water, improve quality of life, and support sustainable development at the local and national levels.